(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The headwaters of five streams on the internal slopes of both the Central and the Western Alps, flowing at altitudes between 2,200 and 2,800 m a.s.l., have been investigated in different years in order to study their stonefly fauna. After having summarised the characteristics of each biotope, giving a list of the collected species, the altitudinal and seasonal clistribution of each species is briefly analysed. From qualitative et semi-quantitative data some observation on high altitude rheophilic communities is briefly given.